2018
DOI: 10.1007/s00604-018-2758-x
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomeric separation of adrenaline, noradrenaline, and isoprenaline by capillary electrophoresis using streptomycin-modified gold nanoparticles

Abstract: Enantiomeric separations of the adrenergic compounds adrenaline, noradrenaline, and isoprenaline were studied. Electromigrative separations were performed in uncoated fused silica capillaries using streptomycin-modified gold nanoparticles (ST-AuNPs) as an additive to the background electrolyte. The ST-AuNPs are shown to serve as an effective chiral selector. The modified AuNPs were characterized in terms of size and zeta potential, and by IR and UV-vis spectra. The effects of ST-AuNP concentration, pH value, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 35 publications
0
22
0
1
Order By: Relevance
“…Molecular modification of the surfaces of gold nanoparticles increases their stability and improves their physicochemical properties and functionality, which means they can be used in more biological chemical reactions to expand their application [52]. Current surface modification methods use covalent bonding [53,54], electrostatic interactions [55], or attachment of a small molecule or compound for specific recognition of the target [56].…”
Section: Functional Modification Of Gold Nanoparticlesmentioning
confidence: 99%
“…Molecular modification of the surfaces of gold nanoparticles increases their stability and improves their physicochemical properties and functionality, which means they can be used in more biological chemical reactions to expand their application [52]. Current surface modification methods use covalent bonding [53,54], electrostatic interactions [55], or attachment of a small molecule or compound for specific recognition of the target [56].…”
Section: Functional Modification Of Gold Nanoparticlesmentioning
confidence: 99%
“…The surface‐assembly monolayer (SAM) of gold–sulfur bond creates a strong and stable linkage for the gold materials and the surface‐modified moieties such as polymers, proteins, and antibodies. The thiol–gold bond manufacturing approach for AuNP has been used in many studies 55,70,72 …”
Section: Enantiomeric Recognition By Chiral Nanoparticlesmentioning
confidence: 99%
“…It was observed that, as compared to monolayer AuNPs film capillary column, the three layer AuNPs film capillary column possess superior enantioseparation performance. Further, in 2018, Liu et al [86] successfully added streptomycin-modified AuNPs in background electrolyte (BGE) solution in CE for the first time to separate a number of drug racemates, such as, adrenaline hydrochloride, noradrenaline bitartrate, and isoprenaline hydrochloride.…”
Section: Enantiomeric Separation By Chiral Nanoparticlesmentioning
confidence: 99%